UPAYA PENINGKATAN STATUS GIZI PADA BALITA STUNTING DENGAN PEMERIKSAAN HB DAN MIKROBIOTA SEBAGAI UPAYA IMPLEMENTASI GERAKAN ANTI STUNTING - Yuningsih, Yuningsih; Sari, Asri Iman; Zannah, Ai Nur (Politeknik Kesehatan Kemenkes malang, 2024)
Stunting, a type of malnutrition that begins in the womb until the first two years of life and is worsened by recurrent infectious diseases after birth. Children in tropical countries experience more worm infections which can cause blood loss through the digestive tract due to the number of bad microbiota in the digestive tract. Cumulatively, bad microbiota can cause malnutrition and blood loss which results in decreased body resistance and causes problems with children's growth and development. The aim of this community service is to examine the presence of gastrointestinal microbiota and HB which is associated with nutritional status in stunted toddlers. The method/stage of the activity is a screening examination starting with anamnese and physical examination, then Hb and feces examinations are carried out on stunted toddlers in the Kaliwates Health Center area, Kebonagung village. The number of stunted toddlers targeted was 17 aged 24 – 60 months out of 30 children whose parents were willing to have their Hb and feces checked. The result of this community service is that the number of bad microbiota is greater than the good microbiota in stunted toddlers and in this condition the Hb levels also decrease. Conclusion: Shifts in the composition of toddlers' intestinal bacteria have been associated with an increase in the number of gastrointestinal infections which resulted in a decrease in Hb levels in stunted toddlers.